Oceanographic studies as the basis for shipyard development at the Fish Landing Port of Sabang - Thaib Rizwan; Rianjuanda Djamani; Ilham Zulfahmi; Ayana Rizki; Razali Thaib; Akhyar Akhyar; Muhammad Muhammad; Rahmat Rizqi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Shipbuilding is one of the marine industries which in development needs to pay attention to various parameters from the sea and land. This research was conducted in March to May 2022 with the aim of identifying the influence of oceanographic factors and water quality on the development of the shipbuilding industry at the fishing port of Sabang City. The oceanographic data used includes tides, wind, bathymetry, and sediment composition observed at 12 station points. The depth and tide data are then processed using QGIS. Wind data was analyzed using the Wind Rose Plot and sediment using the Wentworth scale. Oceanographic factors in Sabang Bay have shown very satisfactory results for the development of fish landing bases. The wind in the waters of Sabang Bay blows northwest with high speeds ranging from 10.00 m/s. The depth of the waters indicates a potential location for ship mooring. Sandy sediment is the most common type of sediment found. The tides that occur in the bay of Sabang are relatively stable. Oceanographic factors in Sabang Bay have shown very satisfactory results for the development of fish landing bases.Keywords:OceanographyShipyardSabang Bay